Characteristics of Algebraic Material in the Course of Mathematics of Primary School (Journal of Pedagogical Inventions and Practices, 2023)
The algebraic material in the course of mathematics of primary school performs an auxiliary function in the study of the basic (arithmetic) content of the program.